Electrocochleographic Responses Before and After Short-Term Suprathreshold Electrical Stimulation in Human Cochlear Implant Recipients. Issue 8 (September 2018) - Hoesli, Marco; Huber, Alexander; Pfiffner, Flurin; Veraguth, Dorothe; Roosli, Christof; Dalbert, Adrian
Abstract : Objective: To assess changes in electrocochleographic (ECoG) responses following short-term suprathreshold electrical stimulation during cochlear implant (CI) telemetry in CI recipients. Methods: Extracochlear ECoG recordings were conducted before and after intraoperative short-term suprathreshold electrical stimulation. Tone bursts at 500, 750, and 1000 Hz as well as clicks were used as acoustic stimuli. Changes of ECoG responses were correlated to calculated maximum electrical charge levels. Results: Fourteen subjects were included. On average, no significant changes of ECoG responses occurred in the earliest postoperative phase; therefore, also following short-term suprathreshold electrical stimulation. However, one subject (S7) showed a decrease of ECoG responses. Neural as well as hair cell components of the ECoG signal were affected. On average, the maximum electrical charge level was 22 nC (range, 15–37 nC). In S7, the maximum electrical charge level was 17 nC. No correlations were found between maximum electrical charge levels and changes of ECoG signals. Conclusion: In a majority of cases, electrophysiological responses to acoustic stimuli remain unchanged in the earliest postoperative phase. However, deterioration of cochlear function occurs in this phase. Neural as well as hair cell components of the ECoG signal are affected. Such deterioration is not associated with unusually high electrical charge levels during CI telemetry. Overall, our results support the notion that an electrical charge applied at levels used in the clinical routine does not have an acute deleterious effect on cochlear function.